Polymorphism of keratin intermediate filament (kif) type i gene association of wool quality traits in Patanwadi, Marwari and Dumba breeds of sheep - AHLAWAT, A R; GAJBHIYE, P U; PRINCE, L L L; SINGH, AMAR; GAJJAR, S G (The Indian Journal of Animal Sciences, 2014)
For the present study, 150 blood samples (50 from each breed, viz. Dumba, Patanwadi and Marwari) were collected randomly from animals located at Sheep Breeding Farm, Morbi, Gujarat. Isolation of genomic DNA was carried out. The genotyping was done with the help of PCR-RFLP. At locus KRT 1.2, studies revealed 3 genotypes, viz. MM, MN and NN with genotype frequencies of 0.74, 0.24 and 0.02; 0.54, 0.42 and 0.04 and 0.64, 0.36 and 0.00 for Marwari, Patanwadi and Dumba breeds, respectively. The overall genotypic frequencies at KRT 1.2 locus for MM, MN and NN were 0.64, 0.34 and 0.02 respectively. The overall allele frequencies for allele M and allele N were 0.81 and 0.19 respectively. In general, the frequency of allele M was higher that of allele N in all 3 breeds. The genotypic frequencies of MM were higher than MN and NN in all the three breeds. In KIF gene, all 3 breeds showed no significant deviation from Hardy Weinberg Equilibrium.